APOE and Alzheimer’s Disease: Neuroimaging of Metabolic and Cerebrovascular Dysfunction - Brandon, Jason A.; Farmer, Brandon C.; Williams, Holden C.; Johnson, Lance A. (Frontiers in Aging Neuroscience, 2018)
Apolipoprotein E4 is the strongest genetic risk factor for late onset Alzheimer’s Disease (AD) and is associated with impairments in cerebral metabolism and cerebrovascular function. A substantial body of literature now points to E4 as a driver of multiple impairments seen in AD, including blunted brain insulin signaling, mismanagement of brain cholesterol and fatty acids, reductions in blood brain barrier integrity, and decreased cerebral glucose uptake. Various neuroimaging techniques, in particular PET and MRI, have been instrumental in characterizing these metabolic and vascular deficits associated with this important AD risk factor. In the current mini-review, we summarize the known effects of APOE on cerebral metabolism and cerebrovascular function, with a special emphasis on recent findings via neuroimaging approaches.